Interaksi Big Data, Kualitas Data, dan Kinerja Keputusan: Studi Kasus BPJS Kesehatan - Fauzi Purwa Nugraha; Hamzah Ritchi; Zaldy Adrianto (Universitas Pendidikan Indonesia, 2023)
This research was conducted to prove that data quality and big data analytics capability have an influence on decision-making performance, and then have an impact on business process performance. This research is descriptive and verificative in nature, using a survey method. For the purpose of data analysis, the pattern of relationships between variables is measured using the PLS-SEM approach. Evaluation of structural model measurements is carried out by testing the path coefficient, t-statistics, and R-squared value. The collected data was obtained through the distribution of questionnaires, with information technology staff respondents at the BPJS Kesehatan Pusat. The results of the study show that: (1) Data quality has not significant effect on decision-making performance, (2) Big Data Analytics Capability has a positive effect on decision-making performance, (3) Decision-making performance has a positive effect on business process performance.